2005
DOI: 10.1002/marc.200500143
|View full text |Cite
|
Sign up to set email alerts
|

High‐Temperature Crystalline Phases in Nylon 6/Clay Nanocomposites

Abstract: Summary: Nylon 6/clay nanocomposites (N6CN) with different cooling histories were investigated by differential scanning calorimetry (DSC) and variable‐temperature X‐ray diffraction (XRD). Above the melting temperature, new endothermic peaks appeared in the DSC trace for N6CN. All the neat nylon 6 samples presented amorphous XRD patterns when heated up to the melting range. However, for N6CN samples, undefined crystalline structures remained in the substantially molten polymer matrix up to 300 °C.XRD patterns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
(21 reference statements)
1
14
0
Order By: Relevance
“…It could be related to the fact that the clay platelets initiate a heterogeneous nucleation that leads to an increase in the crystallinity of the nanocomposite samples. In general, the crystallinity of nylon‐based nanocomposite is controlled by the type of nylon matrix, molecular weight, clay concentration, and level of clay exfoliation . The crystallinity of the PA6/clay film is in agreement with those reported by Fasihi et al .…”
Section: Resultssupporting
confidence: 89%
“…It could be related to the fact that the clay platelets initiate a heterogeneous nucleation that leads to an increase in the crystallinity of the nanocomposite samples. In general, the crystallinity of nylon‐based nanocomposite is controlled by the type of nylon matrix, molecular weight, clay concentration, and level of clay exfoliation . The crystallinity of the PA6/clay film is in agreement with those reported by Fasihi et al .…”
Section: Resultssupporting
confidence: 89%
“…For annealed PA6 and PA6/clay films, in addition to the presence of sharp endothermic peaks at 220°C, which are due to the melting of α ‐form crystals, other small endothermic peaks are also detected at 175°C and 160°C, respectively. These additional peaks can be attributed to the formation of small crystals during annealing . They were also related by some authors to an enthalpy relaxation process of the interphase between the crystalline and amorphous phases, which can be induced by isothermal crystallization or annealing process.…”
Section: Resultsmentioning
confidence: 74%
“…The γ ‐phase has a pseudo hexagonal structure with the dimensions of a = 0.472, c = 1.688 nm, and γ = 120°, where the twisted chains allow formation of the hydrogen bonds between parallel chains . It has been shown that PA6 crystalline structure depends strongly on processing conditions . In general, lower temperature and faster cooling rate promote γ ‐crystal of PA6 while higher crystallization temperature and slow cooling rate create more α ‐crystal.…”
Section: Resultsmentioning
confidence: 99%
“…To observe the effect of clay loading on mechanical properties of PCN, same polymer and organic modifier (12‐aminolauric acid) containing three different clay loading (3, 6, and 9 wt % of 12‐aminolauric acid based OMMT of the weight of polymer) are synthesized and their nanomechanical properties are evaluated in this work. X‐ray diffraction (XRD)54–65 and differential scanning calorimetry (DSC)66–76 are often used techniques to study the crystallinity of polymeric materials. In this work, the crystallinity of PCN is studied using XRD and DSC to evaluate the change in crystallinity of PCN with respect to pristine polymer and its effect on nanoscale property enhancement of PCN.…”
Section: Introductionmentioning
confidence: 99%